IKLAN RADIO DAN PENGAMBILAN KEPUTUSAN - Hastuti, Nurnawati Hindra (Transformasi, 2011)
Abstrak Radio is one of popular media used to deliver informations to public. Many companies use radio as the tools to spread the informations of their products, whether goods or services, to their consuments.Â The used of radio commercials is affecting decion making procedures from the consuments. Thus, it is very important to evaluate the strategy used by companies to decide which radio would they put their commercials on. Key word :Radio broadcast and decision maker